Effect of Adding Potassium and Organic Fertilizers on the Soil NPK Content and the Productivity of maize (Zea mays L.) - Mohammad Ahmad AL-Sheikh; Omar Abdullah Abdulrazzak; Taha Hammadi Al-Khalifa (Kufa Journal for Agricultural Sciences)
The integrated use of organic and mineral fertilizers is a practical and good way to preserve and sustain soil fertility, which results in increased availability of nutrients in the soil and their absorption by plants, thus increasing crop productivity. Due to the fixation of potassium in the soil, it is necessary to work to increase the vitality of agricultural soil by adding fertilizers. Organic potassium is an important means of increasing the availability of macro- and micro-nutrients. Current research was carried out in a private farm in Deir Ezzor province during the summer season of 2022 with the aim of studying the effect of adding potassium, organic fertilizer, and their interaction, on the soil content of NPK and the productivity of maize (Gouta 82 variety). A factorial experiment was conducted according to a randomized complete block design (RCBD) with three replications. The experiment included two factors: the first was potassium fertilizer (potassium sulfate: 0, 100, 150, 200 kg K.ha-1) and the second was organic fertilizer (sheep manure: 0, 15, 20, 25 tons.ha-1). Results showed that the fourth level of potassium fertilizer was significantly superior in soil content of mineral nitrogen, available phosphorus, and exchangeable potassium. The values ​​were (N: 8.27, P: 12.07, K: 267.81 mg.kg-1), and the fourth level of organic fertilizer was significantly superior to the studied soil indicators (N: 8.97, P: 12.90, K: 262.79 mg.kg-1), while the values ​​decreased in the control. In the studied plant characteristics (plant height, leaf surface area, grain yield), there is a superiority of the fourth level of potassium and organic fertilizers separately. At the remaining levels and in the control, the values ​​in potassium fertilizer were (180.98 cm, 6147.90 cm2, 7.49 tons.ha-1) respectively. In organic fertilizer, plant characteristics reached (183.49 cm, 6191.50 cm2, 7.72 tons.ha-1) at the fourth level. The interaction of the two fertilizers also had a positive effect on all soil indicators studied, as the interaction of the fourth level of potassium fertilizer with the fourth level of organic fertilizer achieved significant superiority over the rest of the interaction treatments and over the non-fertilized control (N: 9.60, P: 13.76, K: 288.27 mg. kg-1). Likewise, with regard to plant characteristics, interfering the third levels (150 kg/ha) and fourth levels (200 kg/ha) of potassium fertilizer with the fourth level (25 tons/ha) of organic fertilizer achieved the best results (186.92 - 188.20 cm, 6296.15 - 6343.98 cm2, 8.32- 8.36 tons.h-1).